2023
DOI: 10.3390/socsci12020109
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Exhaustion and Engagement in Higher Education Students during a Crisis, Lessons Learned from COVID-19 Experience in Italian Universities

Abstract: Italian university students face an uncertain future characterised by a competitive neoliberal academic environment with high demands and a weak labour market that often cannot hire those who are best qualified. The COVID-19 pandemic has exacerbated students’ uncertainty and negatively affected their well-being. The purpose of this study is to explore perceptions of academic life during the pandemic and to examine the relationship between study load, reduced academic performance, internet addiction, academic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(91 reference statements)
0
9
0
1
Order By: Relevance
“…Several studies, in fact, highlighted how ageing is positively related to the development of coping strategies related to stress management. A study carried out during the pandemic (Ghislieri et al 2023), showed that older students are less exhausted and more engaged than their colleagues younger, so they seem to be able to recover resources useful to build their own academic and professional paths.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, in fact, highlighted how ageing is positively related to the development of coping strategies related to stress management. A study carried out during the pandemic (Ghislieri et al 2023), showed that older students are less exhausted and more engaged than their colleagues younger, so they seem to be able to recover resources useful to build their own academic and professional paths.…”
Section: Discussionmentioning
confidence: 99%
“…El tecnoestrés y el DA no son propios de los estudiantes y docentes de la Educación Básica Regular del Perú (EBR), sino también de aquellos que ya egresaron y que ahora se encuentran cursando estudios superiores para tener oportunidades de crecimiento personal y familiar; bajo los enfoques de derecho, inclusión, equidad, igualdad de género y respeto por la diversidad humana se precisa incluirlos, ya que éste se constituye como el actual potencial humano de la nación, siendo importante su acompañamiento y labor tutorial (Ghislieri et al, 2023).…”
Section: Criterio éTico -Pedagógicounclassified
“…In this study, the causes and descriptions of individual respondents' conditions related to stress management were not investigated Int J Public Health Sci ISSN: 2252-8806  further. However, efforts to prevent CVS related to emotional exhaustion were needed to be recommended, including socialization efforts related to stress management that could be carried out by the student affairs unit or other related units [27]. In addition, socialization related to maintaining a healthy lifestyle and doing regular physical activity was also necessary to reduce stress and minimize burnout [28].…”
Section: Risk Factors Of Cvsmentioning
confidence: 99%